(untitled) (Global Journal of Medical Research, 2019)
The Bohring-Opitz syndrome (BOPS) was first described in 1999 by Bohring et al (1). It is an extremely rare genetic condition, of unknown prevalence, which is caused by de novo or nonsense mutations in the ASXL1 gene. To date 46 people with BOPS have been described, of whom only 20 have a confirmed molecular diagnosis. The BOPS diagnosis is established by clinical suspicion and / or identification of a constitutional heterozygous pathogenic variant in the ASXL1 gene (2). This article shows the first case in Latin America of BOPS confirmed by molecular diagnosis.